FeNi-LDH / L-NCP / NF composite material and preparation method and application thereof

Through the preparation of FeNi-LDH/L-NCP/NF composite materials, the problems of structural collapse and insufficient bidirectional catalytic performance of electrolytic water catalysts were solved, and efficient electrocatalytic activity and stability were achieved.

CN119352088APending Publication Date: 2025-01-24GUANGDONG UNIV OF TECH +1

Patent Information

Application Number
CN202411502149.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing electrolytic composite oxygen-excited catalysts have problems such as structural collapse and agglomeration during the catalytic process and cannot show excellent OER and HER performance at the same time.

Method used

Adopt the preparation method of FENI-LDH/L-NCP/NF composite material, phosphorify through the L-CO-ZIF/NF precursor and sodium hyccythum phosphate, and then conduct a feeni-ldh layered structure to build a unique construction of FENI-LDH. The three -dimensional interface is to improve the conductivity and structural stability.

Benefits of technology

It realizes the excellent HER and OER electrocatalyst activity in the alkaline medium, and the activity of activity has no significant attenuation after 1,000 CV cycles, and has good catalytic stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352088A_ABST
    Figure CN119352088A_ABST
Patent Text Reader

Abstract

The invention discloses a FeNi-LDH / L-NCP / NF composite material and a preparation method and application thereof, and belongs to the technical field of electrocatalyst preparation. The preparation method of the FeNi-LDH / L-NCP / NF composite material provided by the invention comprises the following steps: adding foamed nickel into an aqueous solution of Co (NO3) 2.6 H2O and 2-methylimidazole, and reacting at room temperature to obtain an L-Co-ZIF / NF precursor; the L-Co-ZIF / NF precursor and sodium hypophosphite are subjected to calcination treatment, and L-NCP / NF is obtained; and adding the L-NCP / NF into a mixed aqueous solution of Fe (NO3) 3.9 H2O, Ni (NO3) 3.6 H2O, urea and NH4F, and carrying out a hydrothermal reaction so as to obtain the FeNi-LDH / L-NCP / NF composite material. A unique three-dimensional interface is formed through a layered structure of FeNi-LDH and a network structure of L-NCP, an efficient electron transmission channel is formed, desorption and release of hydrogen can be promoted while protons can be captured, HER and OER in an alkaline medium both show excellent electrocatalytic activity, and meanwhile, the electrochemical performance of the composite material is improved. The composite material has excellent cycling stability after 1000 times of cycling, and has a wide application prospect in hydrogen evolution reaction, oxygen evolution reaction and complete water splitting reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electrocatalyst preparation, and in particular, relates to a FeNi-LDH / L-NCP / NF composite material and a preparation method and application thereof. Background Art

[0002] The complete water splitting consists of the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Due to concentration polarization and other reasons, the actual voltage is higher than the theoretical value, resulting in an increase in the consumption of additional energy. Therefore, it is necessary to prepare a high-efficiency catalyst to effectively reduce the overpotential and improve the catalytic performance. Iron-nickel layered double hydroxide (FeNi-LDH) is a double metal hydroxide with a layered structure, in which metal cations (iron and nickel) and hydroxide anions (OH - ) are arranged alternately to form a layered structure, which has a suitable reaction energy barrier and shows good catalytic activity and application prospects. However, in the process of water electrolysis, Fe 3+ It will randomly dissolve and redeposit on the catalyst surface or be doped into the matrix lattice, and there is a serious Fe dissolution segregation phenomenon, which leads to a sharp decrease in the stability of the catalyst structure collapse. Therefore, it is necessary to improve the existing iron-nickel layered double hydroxide electrode materials to improve their comprehensive performance.

[0003] The prior art with application publication number CN 117512666 A discloses a method for preparing a NiFe LDH@NiCoP / NF water electrolysis oxygen evolution catalyst electrode, which comprises first preparing a NiCo precursor / NF, then calcining and phosphating with sodium hypophosphite to form NiCoP / NF, and then electrodepositing NiFe LDH on the surface of the NiCoP / NF material to obtain a NiFe LDH@NiCoP / NF water electrolysis oxygen evolution catalyst electrode.

[0004] However, the existing composite oxygen evolution catalysts for water electrolysis have the following problems: first, Fe dissolution and segregation can easily lead to structural collapse and agglomeration, resulting in the catalyst being unable to maintain high activity and operation stably for a long time; second, it does not have the ability to simultaneously exhibit excellent OER and HER performance in the same electrolyte. Summary of the invention

[0005] The present application discloses a FeNi-LDH / L-NCP / NF composite material and a preparation method and application thereof, aiming to solve the technical problems that the existing water electrolysis composite oxygen evolution catalyst has structural collapse and agglomeration during the catalytic process and cannot simultaneously exhibit excellent OER and HER performance.

[0006] In order to achieve the above purpose, the technical solution of this application is:

[0007] The first aspect of the present application provides a method for preparing a FeNi-LDH / L-NCP / NF composite material, the preparation method comprising:

[0008] The nickel foam was added into an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole and reacted at room temperature to obtain the L-Co-ZIF / NF precursor;

[0009] The L-Co-ZIF / NF precursor is calcined with sodium hypophosphite to obtain L-NCP / NF;

[0010] The L-NCP / NF is added into a mixed aqueous solution of Fe(NO3)3·9H2O, Ni(NO3)3·6H2O, urea and NH4F to carry out a hydrothermal reaction, thereby obtaining a FeNi-LDH / L-NCP / NF composite material.

[0011] In combination with the first aspect, preferably, the mass ratio of Co(NO3)2·6H2O to 2-methylimidazole is 0.6-0.7:1.3-1.5.

[0012] In combination with the first aspect, preferably, the mass ratio of the sodium hypophosphite added to the L-Co-ZIF / NF precursor is 1-2:1.

[0013] In combination with the first aspect, preferably, the molar ratio of Fe(NO3)3·9H2O to Ni(NO3)3·6H2O, urea and NH4F added is 1:2-3:5:5.

[0014] In combination with the first aspect, preferably, when the nickel foam is added to an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole, the reaction time at room temperature is 4-6 hours.

[0015] In combination with the first aspect, preferably, when the L-Co-ZIF / NF precursor and sodium hypophosphite are calcined, the calcination is carried out in a tubular furnace, the L-Co-ZIF / NF precursor is placed at the front end of the tubular furnace, and the sodium hypophosphite is placed at the rear end of the tubular furnace.

[0016] In combination with the first aspect, preferably, when the L-Co-ZIF / NF precursor is calcined with sodium hypophosphite, the temperature is 300-380° C. and the time is 1.5-3 h.

[0017] In combination with the first aspect, preferably, when the L-NCP / NF is added to a mixed aqueous solution of Fe(NO3)3·9H2O and Ni(NO3)3·6H2O, urea and NH4F for hydrothermal reaction, the temperature is 110-130°C and the time is 8-12h.

[0018] The second aspect of the present application provides a FeNi-LDH / L-NCP / NF composite material prepared by the preparation method described in the first aspect.

[0019] The third aspect of the present application provides the use of the FeNi-LDH / L-NCP / NF composite material described in the second aspect in hydrogen evolution reaction, oxygen evolution reaction and complete water splitting reaction.

[0020] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0021] The preparation method of the FeNi-LDH / L-NCP / NF composite material provided in the present application is to use L-Co-ZIF / NF precursor as a sacrificial template, carry out phosphating treatment with sodium hypophosphite, and then compound the FeNi-LDH layered structure in the system through a hydrothermal reaction. On the one hand, the layered structure of FeNi-LDH and the network structure of L-NCP form a unique three-dimensional interface, constitute an efficient electron transmission channel, promote charge transfer, and thus improve the conductivity of the material. At the same time, the L-NCP prepared by the ZIF-guided strategy has a stable structure and uniform distribution, so that the structure of the composite material is not easy to collapse; on the other hand, the prepared composite material can promote the desorption and release of hydrogen while capturing protons, promote the combination of metal and hydroxyl groups to become HER and OER active sites, so that the HER and OER in alkaline media both show excellent electrocatalytic activity; at the same time, after 1000 CV cycles, the activity after the HER and OER reactions did not decay significantly, and had good catalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 A process flow chart of the Al-FeNi-LDH / L-NCP / NF composite material prepared in the embodiment of the present application;

[0024] Figure 2 Scanning electron microscope images of the FeNi-LDH / NF composite material and the A1-FeNi-LDH / L-NCP / NF composite material prepared in the examples of the present application;

[0025] Figure 3 This is a SEM-mapping image of the Al-FeNi-LDH / L-NCP / NF composite material prepared in the example of the present application;

[0026] Figure 4 XRD patterns of the Al-FeNi-LDH / L-NCP / NF composite material, FeNi-LDH / NF composite material, L-NCP / NF composite material and NF prepared in the examples of the present application;

[0027] Figure 5 HER electrochemical performance diagram of A1-FeNi-LDH / L-NCP / NF composite material, FeNi-LDH / NF composite material, L-NCP / NF composite material and NF prepared in the examples of the present application;

[0028] Figure 6 OER electrochemical performance diagram of A1-FeNi-LDH / L-NCP / NF composite material, FeNi-LDH / NF composite material, L-NCP / NF composite material and NF prepared in the examples of the present application. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0031] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0032] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0033] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0034] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0035] In a first aspect, the present application provides a method for preparing a FeNi-LDH / L-NCP / NF composite material, the preparation method comprising:

[0036] The nickel foam was added into an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole and reacted at room temperature to obtain the L-Co-ZIF / NF precursor;

[0037] The L-Co-ZIF / NF precursor is calcined with sodium hypophosphite to obtain L-NCP / NF;

[0038] The L-NCP / NF is added into a mixed aqueous solution of Fe(NO3)3·9H2O, Ni(NO3)3·6H2O, urea and NH4F to carry out a hydrothermal reaction, thereby obtaining a FeNi-LDH / L-NCP / NF composite material.

[0039] Among them, on the one hand, the layered structure of FeNi-LDH and the network structure of L-NCP form a unique three-dimensional interface, which constitutes an efficient electron transmission channel, promotes charge transfer, and thus improves the conductivity of the material. At the same time, the L-NCP prepared by the ZIF-guided strategy has a stable structure and uniform distribution, making the composite material structure not easy to collapse; on the other hand, the prepared composite material can promote the desorption and release of hydrogen while capturing protons, and promote the combination of metal and hydroxyl groups to become HER and OER active sites, so that both HER and OER in alkaline media show excellent electrocatalytic activity; at the same time, after 1000 CV cycles, the activity after HER and OER reactions did not decay significantly, and it has good catalytic stability.

[0040] It should be noted that the L-NCP derived from the L-Co-ZIF material through the ZIF template-guided strategy in this application is arranged in an orderly manner and has a unique morphology, which effectively solves the problem of easy aggregation and poor dispersibility of the composite material. The ZIF template has a highly controllable structure and can produce a porous morphology. The central atom of ZIF is metal Co, which makes them a material for preparing an ordered and unique morphology; after phosphating, a phosphating film is formed by introducing phosphorus elements to change the surface properties of the material without affecting the macroscopic structure of the material. The phosphating film has good adhesion and wettability, which improves the binding force between FeNi-LDH and L-Co-ZIF, thereby forming a more stable composite structure; the FeNi-LDH layered structure is compounded in the system by a hydrothermal method, and the surface is reconstructed and more active sites are exposed, thereby improving the electrocatalytic activity in the water electrolysis reaction.

[0041] It should be noted that this application uses nickel foam (NF) as the substrate material. First, the surface of the nickel foam is pretreated: acetone solution is added to a beaker, the surface of the nickel foam is soaked, and ultrasonic is performed for 20 minutes to remove organic matter on the surface of the nickel foam; then 2mol / L HCl is ultrasonicated for 5 minutes, and finally deionized water is ultrasonicated several times until the pH reaches neutral, and then placed in a 60°C oven for drying for 24 hours for standby use. NF has a high specific surface area, which enables nickel foam to provide a larger reaction area in electrochemical applications, thereby improving the electrocatalytic performance and effectively reducing the energy consumption of the electrochemical reaction. And it is formed by interconnected channels, and the conductive structure inside these channels can improve the transmission of electrons on the substrate, increase its conductivity, and thus improve the efficiency and rate of the electrocatalytic reaction.

[0042] It should be noted that the preparation process of the present application is made by ZIF template-guided strategy and hydrothermal method. First, nickel foam is added to an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole, reacted at room temperature, and L-Co-ZIF / NF precursor is obtained. Then, the L-Co-ZIF / NF precursor is calcined with sodium hypophosphite to obtain L-NCP / NF; the phosphide derived from L-Co-ZIF material by ZIF template-guided strategy inherits the polyhedral morphology of L-Co-ZIF, which is orderly arranged and has a unique morphology. Then, FeNi-LDH is in situ anchored to the surface of L-NCP / NF by hydrothermal method, forming a unique three-dimensional interface, which can promote charge transfer, promote the desorption and release of hydrogen while capturing protons, and promote the combination of metal and hydroxyl groups to become HER and OER active sites, so that both HER and OER in alkaline media show excellent electrocatalytic activity.

[0043] In the embodiment of the present application, the mass ratio of Co(NO3)2·6H2O to 2-methylimidazole is preferably 0.6-0.7:1.4-1.5. Among them, 2-methylimidazole is used as an organic ligand to coordinate with cobalt ions to form a ZIF structure. By controlling the addition ratio of each substance, the precursor of the prepared Co-ZIF can be made with Co-ZIF as a sacrificial template, which has a highly controllable structure and excellent crystallinity.

[0044] In the embodiment of the present application, the mass ratio of the sodium hypophosphite added to the L-Co-ZIF / NF precursor is 1-2:1. Among them, the degree of phosphating reaction can be adjusted by controlling the amount of sodium hypophosphite added. If the amount added is too much, the excess phosphating agent and sodium hypophosphite in the phosphating solution will generate hydrogen, which will affect the uniformity and quality of the reaction; if the amount added is too little, the phosphating reaction rate will be slow, affecting the production efficiency. Therefore, by controlling the amount of sodium hypophosphite added to remain within an appropriate range, it can be ensured that the phosphating reaction is carried out at an appropriate rate.

[0045] In the embodiment of the present application, the molar ratio of Fe(NO3)3·9H2O to Ni(NO3)3·6H2O, urea and NH4F is 1:2-3:5:5; when performing the hydrothermal reaction, the temperature is preferably 110-130°C, more preferably 120°C, and the time is preferably 8-12h, more preferably 10h. Among them, the morphology is regulated by controlling the components, ratios and process conditions of each substance in the hydrothermal method, adding urea as a precipitant, and adding ammonium fluoride as a morphology regulator, so that FeNi-LDH is in situ anchored on the surface of L-NCP / NF, and a spherical structure composed of lamellar structures can be generated and a large number of active sites can be obtained, which greatly promotes the electrocatalytic activity.

[0046] In the embodiment of the present application, the nickel foam is added to the aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole for a room temperature reaction time of preferably 4-6 hours, more preferably 5 hours. Among them, a shorter reaction time leads to insufficient crystallinity and uneven particle size distribution, while a too long time induces unnecessary side reactions and affects the purity of the product. Therefore, by controlling the reaction time, a composite material with a nanosheet array structure can be prepared by a ZIF template-guided strategy.

[0047] In the embodiment of the present application, when the L-Co-ZIF / NF precursor is calcined with sodium hypophosphite, the calcination is carried out in a tubular furnace, and the L-Co-ZIF / NF precursor is placed at the front end of the tubular furnace, and the sodium hypophosphite is placed at the rear end of the tubular furnace. Among them, through this placement method, the L-Co-ZIF / NF precursor is placed at the front end of the tubular furnace, which means that it is first placed in the heating area, and the sodium hypophosphite is placed at the rear end of the tubular furnace. During the heating process, the phosphine gas released by the sodium hypophosphite needs to react with the L-Co-ZIF / NF precursor at the front end at a certain temperature gradient, and can form phosphide on the surface and perform structural modification, and by accurately controlling the temperature distribution and gas flow in the tubular furnace, it provides a basis for the subsequent FeNi-LDH composite.

[0048] In the embodiment of the present application, when the L-Co-ZIF / NF precursor is calcined with sodium hypophosphite, the temperature is preferably 300-380°C and the time is preferably 1.5-3h. Among them, by controlling the temperature and time of calcination, the structure of the substance after the phosphating reaction can be controlled. Too short calcination time may result in incomplete decomposition of the L-Co-ZIF / NF precursor, while too long calcination time may result in destruction of the product structure or unnecessary side reactions.

[0049] The second aspect of the present application provides a FeNi-LDH / L-NCP / NF composite material prepared by the preparation method described in the first aspect. Based on the above preparation process, the composite material can be endowed with a unique three-dimensional interface, and both HER and OER in alkaline media show excellent electrocatalytic activity and structural stability.

[0050] The third aspect of the present application provides the application of the FeNi-LDH / L-NCP / NF composite material described in the second aspect in hydrogen evolution reaction, oxygen evolution reaction and complete water splitting reaction. Based on the unique three-dimensional interface of the above composite material, both HER and OER in alkaline medium show excellent electrocatalytic activity and structural stability. After 1000 CV cycles, the activity after HER and OER reactions has no obvious attenuation, and has good catalytic stability, so that it has a wide range of application prospects in hydrogen evolution reaction, oxygen evolution reaction or complete water splitting reaction of electrolytic water.

[0051] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0052] Example 1

[0053] This embodiment provides a method for preparing an Al-FeNi-LDH / L-NCP / NF composite material. Figure 1 The process flow chart shown in the figure is used for preparation, which specifically includes:

[0054] S101: 0.58 g Co(NO3)2·6H2O and 1.31 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained.

[0055] S102: placing the L-Co-ZIF / NF precursor at the front end of a tube furnace, placing sodium hypophosphite at the rear end of the tube furnace, and calcining at 350°C for 2h in a N2 atmosphere to obtain L-NCP / NF;

[0056] S103: Fe(NO3)3·9H2O and Ni(NO3)3·6H2O in a molar ratio of 1:3, 1.25 mmol urea and 1.25 mmol NH4F were stirred and mixed in 40 mL deionized water, and hydrothermally reacted at 120°C for 10 h to obtain A1-FeNi-LDH / L-NCP / NF composite material.

[0057] Example 2

[0058] This embodiment provides a method for preparing an A2-FeNi-LDH / L-NCP / NF composite material, which specifically includes:

[0059] S201: 0.6 g Co(NO3)2·6H2O and 1.3 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained;

[0060] S202: placing the L-Co-ZIF / NF precursor at the front end of the tube furnace, placing the sodium hypophosphite at the rear end of the tube furnace, and calcining at 350°C for 2h in a N2 atmosphere to obtain L-NCP / NF;

[0061] S203: Fe(NO3)3·9H2O and Ni(NO3)3·6H2O with a molar ratio of 1:2.5, 1.25 mmol urea and 1.25 mmol NH4F were stirred and mixed in 40 mL deionized water, and hydrothermally reacted at 120°C for 10 h to obtain A2-FeNi-LDH / L-NCP / NF composite material.

[0062] Example 3

[0063] This embodiment provides a method for preparing an A3-FeNi-LDH / L-NCP / NF composite material, which specifically includes:

[0064] S301: 0.65 g Co(NO3)2·6H2O and 1.5 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained;

[0065] S302: placing the L-Co-ZIF / NF precursor at the front end of the tube furnace, placing the sodium hypophosphite at the rear end of the tube furnace, and calcining at 350°C for 2h in a N2 atmosphere to obtain L-NCP / NF;

[0066] S303: Fe(NO3)3·9H2O and Ni(NO3)3·6H2O in a molar ratio of 1:2, 1.25mmol urea and 1.25mmol NH4F were stirred and mixed in 40mL deionized water, and hydrothermally reacted at 120°C for 10h to obtain A3-FeNi-LDH / L-NCP / NF composite material.

[0067] At the same time, in order to verify the comprehensive performance of the FeNi-LDH / L-NCP / NF composite material prepared in the above embodiment, the present application provides the following comparative examples for detailed description.

[0068] Comparative Example 1

[0069] This comparative example provides a method for preparing a FeNi-LDH / NF composite material, which specifically includes:

[0070] S401: Fe(NO3)3·9H2O and Ni(NO3)3·6H2O in a molar ratio of 1:3, 1.25mmol urea, 1.25mmol NH4F and NF were stirred and mixed in 40mL deionized water, and hydrothermally reacted at 120°C for 10h to obtain a FeNi-LDH / NF composite material.

[0071] Comparative Example 2

[0072] This comparative example provides a method for preparing a L-NCP / NF composite material, which specifically includes:

[0073] S501: 0.58 g Co(NO3)2·6H2O and 1.31 g 2-methylimidazole were dissolved in deionized water, the two solutions were quickly mixed and clean NF was added. After deposition at room temperature for 5 h, a purple L-Co-ZIF / NF precursor was obtained.

[0074] S502: placing the L-Co-ZIF / NF precursor at the front end of the tube furnace, placing the sodium hypophosphite at the rear end of the tube furnace, calcining at 350°C for 2h in a N2 atmosphere to obtain a L-NCP / NF composite material.

[0075] Comparative Example 3

[0076] The material provided in the comparative example of the present application is subjected to comparative testing using pure nickel foam without compounding FeNi layered double hydroxide and L-NCP, which is recorded as NF.

[0077] In order to verify the morphology and structure of the FeNi-LDH / L-NCP / NF composite material prepared in the example of the present application, the structural performance of the FeNi-LDH / L-NCP / NF composite material prepared in the example was characterized, and the results were as follows: Figure 2-Figure 4 As shown; among them, Figure 2 The scanning electron microscope images of FeNi-LDH / NF composite material and A1-FeNi-LDH / L-NCP / NF composite material; Figure 3 It is the SEM-mapping image of A1-FeNi-LDH / L-NCP / NF composite material; Figure 4 XRD patterns of A1-FeNi-LDH / L-NCP / NF composite, FeNi-LDH / NF composite, L-NCP / NF composite and NF.

[0078] according to Figure 2 As known, it is the scanning electron microscope image of FeNi-LDH / NF composite material and A1-FeNi-LDH / L-NCP / NF composite material, where ab) is FeNi-LDH / NF composite material, cd) is A1-FeNi-LDH / L-NCP / NF composite material. From Figure ab), it can be seen that the morphology of FeNi-LDH / NF under 4000 times magnification is spherical. After the magnification, it can still be observed that it presents a lamellar structure and grows vertically on nickel foam. This arrangement is conducive to the high-quality transmission of electrons. From Figure cd), it can be seen that the morphology of FeNi-LDH / L-NCP / NF is a nanocluster, which is composed of many smooth and uniform flaky nanosheets with a particle size of about 200nm. The wrinkled morphology of FeNi-LDH grown on the surface of L-NCP can increase its specific surface area, which is conducive to the exposure of active sites.

[0079] according to Figure 3 As known, this is the SEM-mapping image of A1-FeNi-LDH / L-NCP / NF composite material. The FeNi-LDH / L-NCP / NF composite material is composed of Ni, Co, Fe, P and O elements, and is uniformly distributed in the composite material.

[0080] according to Figure 4As known, the XRD patterns of L-NCP / NF, FeNi-LDH / NF, FeNi-LDH / L-NCP / NF and NF. The three diffraction peaks at 2θ=44.5°, 51.8° and 76.4° are characteristic peaks of Ni (JCPDS: No.04-0850), and the peaks of L-NCP / NF at 40.98°, 47.57° and 54.43° correspond to NiCoP (111), (210) and (300) crystal planes (JCPDS: No.71-2336), respectively, which proves that NiCoP (denoted as L-NCP / NF) is obtained after phosphating L-Co-ZIF / NF. In addition, the FeNi-LDH / NF peaks at 2θ=11.7°, 23.3°, 34.6°, 39.0° and 61.3° correspond to the (003), (006), (012), (015) and (113) crystal planes of FeNi-LDH, respectively (JCPDS: No.51-0463). Typical diffraction peaks of L-NCP and FeNi-LDH were also observed in FeNi-LDH / L-NCP / NF, proving that the composite material was successfully prepared. In addition, the diffraction peak intensity of FeNi-LDH in the FeNi-LDH / L-NCP / NF composite material is very high, indicating that the crystal form is complete.

[0081] In order to verify the performance of the FeNi-LDH / L-NCP / NF composite material prepared in the example of the present application as a catalyst in water electrolysis, the HER and OER electrocatalytic activity tests were carried out on the FeNi-LDH / L-NCP / NF composite material prepared in the example.

[0082] The Hg / HgO electrode was used as the reference electrode, the graphite rod was used as the counter electrode, and the catalyst prepared in Example 1 was used as the working electrode. Potential reference reversible hydrogen electrode (RHE): E RHE =E Hg / HgO + 0.098 + 0.059 × pH (1M KOH solution). Calculate the overpotential (η): η = E RHE -1.23 V. All electrode potential data were 90% iR compensated.

[0083] In the electrochemical performance test, the three-electrode system was used to test the OER and HER electrocatalytic performance on an electrochemical workstation (CHI760E). When testing, the working electrode was first activated by cyclic voltammetry (CV) at a scan rate of 10mV / s until the CV curves were highly overlapped, the oxygen evolution reaction voltage range was 0 to 1V (vs. RHE), and the hydrogen evolution reaction voltage range was -0.9 to -1.4V (vs. RHE).

[0084] according to Figure 5As is known, the HER electrocatalytic activity of different catalysts was tested in a three-electrode system with 1.0 mol / L KOH electrolyte. Figure 5 As shown in (a), when the current density reaches 10 mA / cm 2 The overpotential is only 106 mV, which is significantly lower than that of L-NCP / NF (172 mV), FeNi-LDH / NF (247 mV) and pure NF (285 mV). The Tafel slope reveals the intrinsic reaction kinetics of HER, such as Figure 5 As shown in (b), the Tafel slope value of FeNi-LDH / L-NCP / NF (58.5mV / dec) is smaller than that of FeNi-LDH / NF (110mV / dec), L-NCP / NF (99.3mV / dec) and NF (265.2mV / dec). This shows that the HER catalytic process of FeNi-LDH / L-NCP / NF follows the Volmer-Heyrovsky reaction mechanism, and its rate-limiting step is the electrochemical desorption process. For the practical application of the catalyst, it is necessary not only to have excellent performance but also excellent stability. The it curve for testing stability is shown in Figure 5 As shown in (c), a chronoamperometric test was performed for 48 hours at a constant current density of 10 mA·cm-2 to evaluate the stability performance, and the current density retention rate was 97.5%. Figure 5 (d) is the cycling performance test of FeNi-LDH / L-NCP / NF, comparing the change in overpotential of the material in the initial state and after 1000 CV cycles by linear sweep voltammetry. 2 The overpotential at the current density increased by 8 mV, indicating that FeNi-LDH / L-NCP / NF has good cycling stability as a HER catalyst.

[0085] according to Figure 6 As far as we know, the OER electrocatalytic activity of different catalysts was tested in a three-electrode system with 1.0 mol / L KOH electrolyte. The FeNi-LDH / L-NCP / NF composite material was 2 The overpotential at 10 mV / cm2 was 220 mV, showing good OER catalytic activity, while FeNi-LDH / NF, L-NCP / NF, and NF 2 The overpotentials at the current density are all relatively high, requiring 275, 246, and 398 mV ( Figure 6 (a)). In addition, Figure 6(b) It can be seen that the Tafel slope corresponding to the above catalysts is used to evaluate the OER kinetics of the catalyst. The Tafel slope represents the rate at which the overpotential changes with the increase of current density. The smaller the value, the faster the intrinsic kinetics of the reaction and the better the electrocatalytic performance. The Tafel slope of the FeNi-LDH / L-NCP / NF composite material is 72.5mV / dec, which is much lower than the Tafel slopes of FeNi-LDH / NF (89.5mV / dec), L-NCP / NF (85.2mV / dec) and NF (285.3mV / dec) materials. The results show that the FeNi-LDH / L-NCP / NF composite material has the best kinetic performance. The stability of the material was tested using chronoamperometry, as shown in Figure 2. Figure 6 (c) is the chronoamperometric test of the FeNi-LDH / L-NCP / NF composite material. After 48 hours of continuous current testing, the current density did not show a significant decrease, and the current density retention rate was 98.2%, which indicates that the material has good stability. Figure 6 As shown in (d), after 1000 CV cycles, the LSV curve of the FeNi-LDH / L-NCP / NF composite material almost coincides with the initial LSV curve of the reaction, which indicates that its activity has not been significantly attenuated after 1000 CV cycles, and the OER current density retention rate is 96.7%, further confirming that the FeNi-LDH / L-NCP / NF composite material has good catalytic stability in OER in alkaline electrolyte.

[0086] Therefore, the FeNi-LDH prepared by the ZIF template-guided strategy and hydrothermal method was loaded onto the L-NCP derived from L-Co-ZIF phosphating to obtain the FeNi-LDH / L-NCP / NF composite material. 2 When , the HER and OER overpotentials are 106mV and 220mV respectively. 2 The capacitance retention rates after 48 hours of continuous operation at the current density were 97.5% and 98.2%, respectively. This is because the layered structure of FeNi-LDH and the network structure of L-NCP form a unique three-dimensional interface, which constitutes an efficient mass transfer channel, promotes charge transfer, and greatly promotes the decomposition of water. It has broad application prospects in hydrogen evolution reaction, oxygen evolution reaction and complete water splitting reaction.

[0087] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0088] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A method for preparing a FeNi-LDH / L-NCP / NF composite material, characterized in that: The preparation method comprises: The nickel foam was added into an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole and reacted at room temperature to obtain the L-Co-ZIF / NF precursor; The L-Co-ZIF / NF precursor is calcined with sodium hypophosphite to obtain L-NCP / NF; The L-NCP / NF is added into a mixed aqueous solution of Fe(NO3)3·9H2O, Ni(NO3)3·6H2O, urea and NH4F to carry out a hydrothermal reaction, thereby obtaining a FeNi-LDH / L-NCP / NF composite material.

2. The method for preparing the FeNi-LDH / L-NCP / NF composite material according to claim 1, characterized in that: The mass ratio of the Co(NO3)2·6H2O to 2-methylimidazole is 0.6-0.7:1.3-1.

5.

3. The method for preparing the FeNi-LDH / L-NCP / NF composite material according to claim 1, characterized in that: The mass ratio of the sodium hypophosphite added to the L-Co-ZIF / NF precursor is 1-2:

1.

4. The method for preparing the FeNi-LDH / L-NCP / NF composite material according to claim 1, characterized in that: The molar ratio of Fe(NO3)3·9H2O to Ni(NO3)3·6H2O, urea and NH4F is 1:2-3:5:

5.

5. The method for preparing the FeNi-LDH / L-NCP / NF composite material according to claim 1, characterized in that: When the nickel foam is added to an aqueous solution of Co(NO3)2·6H2O and 2-methylimidazole, the reaction time at room temperature is 4-6 hours.

6. The method for preparing the FeNi-LDH / L-NCP / NF composite material according to claim 1, characterized in that: When the L-Co-ZIF / NF precursor and sodium hypophosphite are calcined in a tubular furnace, the L-Co-ZIF / NF precursor is placed at the front end of the tubular furnace, and the sodium hypophosphite is placed at the rear end of the tubular furnace.

7. The method for preparing the FeNi-LDH / L-NCP / NF composite material according to claim 1, characterized in that: When the L-Co-ZIF / NF precursor is calcined with sodium hypophosphite, the temperature is 300-380° C. and the time is 1.5-3 hours.

8. The method for preparing the FeNi-LDH / L-NCP / NF composite material according to claim 1, characterized in that: When the L-NCP / NF is added to a mixed aqueous solution of Fe(NO3)3·9H2O, Ni(NO3)3·6H2O, urea and NH4F for hydrothermal reaction, the temperature is 110-130°C and the reaction time is 8-12 hours.

9. A FeNi-LDH / L-NCP / NF composite material prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the FeNi-LDH / L-NCP / NF composite material according to claim 9 in hydrogen evolution reaction, oxygen evolution reaction and overall water splitting reaction.

Citation Information

Patent Citations

  • Preparation method of NiFe LDH coated NiCoP / NF water electrolysis oxygen evolution catalyst electrode

    CN117512666A

Cited By

  • Simple preparation method of Ni2P / Fe3P electrocatalyst and application of Ni2P / Fe3P electrocatalyst in industrial hydrogen production

    CN120443248A